KAPASITAS LENTUR BALOK BETON BERTULANG DENGAN MENGGUNAKAN AGREGAT KASAR TEMPURUNG KELAPA - Suarnita, I Wayan (JOURNAL TEKNIK SIPIL DAN INFRASTRUKTUR, 2013)
Beam and plate are dominant element of a reinforced concrete building which experience pressure and flexural moment due to gravity which are live and dead loads. This research aims to find out the value of flexural capacity of reinforced concrete beam using coconut shell as coarse aggregate. The laboratory test results and the theoretical result were compared. In this research, beam of 175 x 350 x 1400 mm were used, the identical push-load used were 2 D 5,6Â  mm and variation of the number of tensile reinforcement were 4 D 7,8 mm; 5 D 7,8 mm, and 6 D 7,8 mm. Each variation is presented in three samples. Hence, resulting different maximum loads.The result obtained as concrete unit weight, which are 1,773 gr/cm3, push-load strength of 13,59 MPa, average flexural capacity of 95 kN for BL 41 to BL 43 and 115 kN for BL 51 to BL 63. The result of flexural capacity of BL 51 to BL 63 was not fully reached due to incompetency of the testing instrument. Â  Keywords: flexural capacity, beam, coconut shell concrete